The Effect of Spirituality on Fraud Prevention: Internal Control as an Intervening Variable - Amalia, Firda Ayu; Wicaksono, Agung Prasetyo Nugroho; Hanif, Ahmad Faishal; Junaidi, Muhammad Hilman (Journal of Accounting and Finance Management, 2024)
This study examines whether spirituality has an effect on fraud prevention with internal control as an intervening variable. This research is an associative descriptive research. The population used was all employees of the Most District Offices of Kediri Regency using the quota sampling technique determined by the researcher as many as 91 respondents. In this study using the PLS analysis method through the SEM approach and supported by SmartPLS 3.0 software. The results of the study show that Spirituality has a significant effect on internal control and fraud prevention. Furthermore, spirituality has a significant effect on fraud prevention with internal control as an intervening variable.